2001
DOI: 10.1016/s0014-5793(01)02679-5
|View full text |Cite
|
Sign up to set email alerts
|

Growth kinetics rather than stress accelerate telomere shortening in cultures of human diploid fibroblasts in oxidative stress‐induced premature senescence

Abstract: WI-38 human diploid fibroblasts underwent accelerated telomere shortening (490 bp/stress) and growth arrest after exposure to four subcytotoxic 100 W WM tert-butylhydroperoxide (t-BHP) stresses, with a stress at every two population doublings (PD). After subcytotoxic 160 W WM H 2 O 2 stress or five repeated 30 W WM t-BHP stresses along the same PD, respectively a 322 þ 55 and 380 þ 129 bp telomere shortening was observed only during the first PD after stress. The percentage of cells resuming proliferation afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 13 publications
4
24
0
Order By: Relevance
“…These findings were also backed up similar observations using IMR90 cells expressing telomerase (Gorbunova et al 2002). Another study showed that by using multiple discontinuous subcytotoxic tert-butylhydroperoxide (t-BHP) or a single subcytotoxic H 2 O 2 treatment in WI-38 fibroblasts, a significant increase in rates of telomeres erosion was detected (Dumont et al 2001;de Magalhaes et al 2002). However, this was accounted for by the cell division of a small proportion of cells that resumed proliferation following treatment and contributed disproportionally to the increase in the PD of the culture as a whole.…”
Section: Discussionsupporting
confidence: 67%
“…These findings were also backed up similar observations using IMR90 cells expressing telomerase (Gorbunova et al 2002). Another study showed that by using multiple discontinuous subcytotoxic tert-butylhydroperoxide (t-BHP) or a single subcytotoxic H 2 O 2 treatment in WI-38 fibroblasts, a significant increase in rates of telomeres erosion was detected (Dumont et al 2001;de Magalhaes et al 2002). However, this was accounted for by the cell division of a small proportion of cells that resumed proliferation following treatment and contributed disproportionally to the increase in the PD of the culture as a whole.…”
Section: Discussionsupporting
confidence: 67%
“…24 Furthermore, the view that attrition of telomeres is a marker for the oxidative stress-induced senescent cell phenotype has recently been questioned. 12,25,26 Although it has been demonstrated that proatherogenic factors inactivate telomerase in HUVECs, whereas NO activates telomerase, 19,27 it is generally true that human cells express rather low levels of telomerase activity. 23 Collectively, our findings suggest that additional mechanism(s) are operant in inducing premature endothelial cell senescence and/or that premature senescence is mechanistically distinct from replicative endothelial cell senescence.…”
Section: Discussionmentioning
confidence: 99%
“…46 DNA strand breaks induced by oxidative stress or topoisomerase inhibitors cause poly (ADP-ribose) polymerase (PARP) hyperactivation and subsequent NAD + depletion, leading to apoptosis [10,11]. Sublethal H 2 O 2 (< 0.45 mM) treatment of human fibroblasts caused growth arrest [4] and induced a senescent-like phenotype [12][13][14]. However, the role of DNA strand breaks induced by sublethal oxidative stress in cellular senescence is unknown.…”
Section: Introductionmentioning
confidence: 99%